2004
DOI: 10.1007/s00213-004-2042-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural reward-related learning in rats with neonatal ventral hippocampal lesions and prior cocaine exposure

Abstract: Rational-Psychostimulant injections in rats have been shown to alter future performance in natural reward conditioning. These effects may represent a persistent impact of drugs on neurocircuits that interface cognitive and motivational processes, which may be further altered in neuropsychiatric conditions that entail increased addiction vulnerability.Objective-This study investigated whether a rat model of schizophrenia with cocaine addiction vulnerability shows altered natural reward conditioning with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…High FLETR values in NVHL rats captures two clinical attributes of schizophrenia patients: over-consumption of carbohydrate enriched-foods and cognitive deficits (McCreadie 2003). High FLETR values are also consistent with how NVHLs show increased natural-reward related impulsivity and behavioral disinhibition (Chambers et al 2005; Chambers and Self 2002; Placek et al 2013; Tseng et al 2008) in parallel to PFC-based deficits in decision-making in schizophrenia patients (Heerey et al 2008). …”
Section: Discussionsupporting
confidence: 52%
“…High FLETR values in NVHL rats captures two clinical attributes of schizophrenia patients: over-consumption of carbohydrate enriched-foods and cognitive deficits (McCreadie 2003). High FLETR values are also consistent with how NVHLs show increased natural-reward related impulsivity and behavioral disinhibition (Chambers et al 2005; Chambers and Self 2002; Placek et al 2013; Tseng et al 2008) in parallel to PFC-based deficits in decision-making in schizophrenia patients (Heerey et al 2008). …”
Section: Discussionsupporting
confidence: 52%
“…NVHLs impact the maturation and function of prefrontal cortical-ventral striatal circuits to which the ventral hippocampus directly projects, in multiple ways that correspond to neural and behavioral findings in human schizophrenia and subjects with addictions ( Liu et al 1998 ; Chambers et al 2001 ; Heerey, Bell-Warren & Gold 2008 ; Tseng et al 2009 ). Behaviorally, NVHL rats show baseline cognitive impulsivity in their approach to natural rewards that is worsened by prior cocaine history ( Chambers et al 2005 ), mirroring impulsivity found in populations with nicotine dependence and other addictions ( Bickel, Odum & Madden 1999 ). The present study identified impulsive and perseverative styles of nicotine seeking in the NVHL model like those previously shown in cocaine self-administration ( Chambers & Self 2002 ).…”
Section: Discussionmentioning
confidence: 98%
“…Behaviorally, NVHL rats show baseline cognitive impulsivity in their approach to natural rewards that is worsened by prior cocaine history (Chambers et al, 2005), mirroring impulsivity found in populations with nicotine dependence and other addictions (Bickel et al, 1999). The present study identified impulsive and perseverative styles of nicotine seeking in the NVHL model like those previously shown in cocaine self-administration (Chambers and Self, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…In turn, these circuits and their motivational functions are modulated by the status of the hippocampus (Chambers et al, 2005, 2001, 2010). At the focal point of this anatomy, the NAC is the epicenter of information processing and memory that generates an animal’s motivational–behavioral repertoire.…”
Section: Low Neurogenic States and Addiction Vulnerabilitymentioning
confidence: 99%